PROSPEK MADRASAH DI INDONESIA: ANALISIS POLITIK PENDIDIKAN - Pradi Khusufi Syamsu (Pascasarjana UIN Siber Syekh Nurjati Cirebon, 2017)
AbstractThis paper confirms that the politics of national education has a strong influence on the development of madrasah in Indonesia. Even marginalized by the political madrassa education in Indonesia who are concerned and care about the school system. As a result, the alumni madrasas are not allowed to compete with school graduate or equivalent. Attempts to obtain state recognition done by the madrasah. Madrasah was slightly gained recognition with the publication of the Joint Decree (SKB) Three Ministers in 1975. The government's political orientation in 1980 until the 1990s that is more accommodating to Muslims make significant changes to the current madrasah trip.The climax, the school became part of the educational system after the enactment of the National Education System Law no. 20 in 2003. However, the true struggle madrasah to be part of the national education system is not free. There is a cost to be paid by the madrasah for recognition. Knowingly or not, almost like the madrasah school curriculum even more such as school. Madrasah has lost the spirit. Islamic sciences trimmed, on the pretext of simplification, for recognition. So, it is too early to conclude that the struggle madrasah was over. Madrasah should be part of the national education system, but do not lose the spirit and erode the values and teachings of his religion.Keywords: Politic, National Education, Madrasah, School.Â AbstrakTulisan ini menegaskan bahwa politik pendidikan nasional memiliki pengaruh kuat terhadap perkembangan madrasah di Indonesia. Bahkan madrasah termarginalkan oleh politik pendidikan Indonesia yang mementingkan dan mempedulikan sistem sekolah. Akibatnya, alumni madrasah tidak diperkenankan untuk bersaing dengan lulusan sekolah yang sederajat. Upaya untuk mendapatkan pengakuan negara dilakukan oleh madrasah. Madrasah pun sedikit mendapat pengakuan dengan terbitnya Surat Keputusan Bersama (SKB) Tiga Menteri tahun 1975. Orientasi politik pemerintah tahun 1980 hingga 1990-an yang lebih akomodatif terhadap umat Islam membuat perubahan yang cukup signifikan terhadap perjalanan madrasah saat itu.Puncaknya, madrasah menjadi bagian dari sistem pendidikan setelah disahkannya Undang-Undang Sistem Pendidikan Nasional no. 20 tahun 2003. Namun, sejatinya perjuangan madrasah untuk menjadi bagian dari sistem pendidikan nasional tidaklah gratis. Ada cost yang harus dibayar oleh madrasah untuk mendapat pengakuan. Disadari atau tidak, madrasah nyaris mirip sekolah secara kurikulum bahkan makin tersekolahkan. Madrasah telah kehilangan ruh. Ilmu-ilmu keislaman dipangkas, dengan dalih penyederhanaan, untuk mendapat pengakuan. Maka, terlalu dini menyimpulkan bahwa perjuangan madrasah telah usai. Madrasah harus menjadi bagian sistem pendidikan nasional namun tidak kehilangan ruh dan terkikis nilai-nilai serta ajaran-ajaran agamanya.Kata Kunci: Politik, endidikan Nasional, Madrasah, Sekolah.